A methodology for implementation of service learning in higher education institution: A case study from faculty of computer science and information technology, UNIMAS - Nadianatra, Musa; Dayang Hanani, Abang Ibrahim; Johari, Abdullah; Suhaila, Saee; Fatihah, Ramli; Abdul Rahman, Mat; Mohd Johan, Ahmad Khiri (Universiti Teknikal Malaysia Melaka, 2017)
Service learning is a teaching and learning approach that includes an aspect of community service within an academic course with instruction and reflection, with the objective to enrich students’ learning experience. This is in line with the aspiration of the Malaysian government to produce well-rounded and holistic graduates and included in Shift 1 of the Malaysia Education Blueprint 2015-2025 (Higher Education). There are various challenges in the implementation of a service learning program, with the involvement of many stakeholders and local culture and nature of the specific community. Therefore, this paper proposed a methodology for the implementation of a service learning program, within an academic course, taking into consideration of various stakeholders and the needs of the community. This paper also presented the case study based on the application of the methodology at the faculty. Having a sound methodology has minimised the issues during the implementation, and could be applied by other interested parties.